Percepción del aprendizaje y entorno educativo en las guardias hospitalarias por los médicos residentes de un hospital terciario del Seguro Social - Vásquez-Alva, Rolando (2024)
Introduction. The educational environment in hospital medical services has an impact on the resident physician’s training, performance, satisfaction and skillsacquisition. Objectives. To know the resident physician’s perception of the learning and educational environment and associated factors during duties in theEmergency Department of Hospital EsSalud Edgardo Rebagliati Martins, Lima, during April-May 2019. Methods. Observational, cross-sectional study,applying Postgraduate Hospital Educational Environment Measure (PHEEM) instrument, to resident physicians of medical specialties who perform dutiesin Emergency Department. Population, 141 residents, obtaining 131 surveys. Results. Average age 30.74 years. Male sex 57.25%. From Lima 52.67%.Undergraduate in National University 45.04%. Specialties: critical areas 21.37%, internal medicine 25.2%, other medical specialties 53.44%. PHEEM score: 87.31 (62.60% of respondents), as an educational environment more positive than negative, with room for improvement. Dimensions score: Autonomy role 30.32 with a more positive perception of one’s work. Teaching, 30 with need for some retraining. Social support, 26.99 as a place of more pros than cons. Factors associated with autonomy role, sex (p=0.037). In multivariate model, male residents had a more positive perception of each other’s work (ORc=2.125(1.040-4.339), ORA=2.513 (1.182-5.341). In Perception of teaching, sex had significant association (p=0.021) and type of undergraduate university (p=0.051).In multivariate model, male residents were more likely to better perceive the level of teaching ORc=2.290 (1.124-4.668), ORA=2.093 (1.019-4.320).Conclusion. Resident physicians perceive the positive aspects in the educational environment (autonomy, teaching and social support) in hospital on-calls in the Emergency Department of a tertiary hospital of the Social Security.